Ethics for medical students - Adhikari, Ramesh Kant (Journal of Institute of Medicine Nepal, 2009)
The full text of this paper is available from the <a title="http://www.jiom.com.np/index.php?journal=jiomjournal&page=article&op=view&path[]=352&path[]=348" href="http://www.jiom.com.np/index.php?journal=jiomjournal&page=article&op=view&path[]=352&path[]=348" target="_blank">Journal of Institute of Medicine website Journal of Institute of Medicine, December, 2008; 30:3 1-2